623 PERCUTANEOUS LEFT ATRIAL APPENDAGE CLOSURE AND TRANSCATHETER CEREBRAL EMBOLIC PROTECTION: TWO CASES REPORT. (15th December 2022) - Roccabruna, Alessandra; Fanti, Diego; Guarracini, Fabrizio; Muraglia, Simone; D´onghia, Giovanni; Casagranda, Giulia; Bonmassari, Roberto; Ribichini, Falvio Luciano
Abstract: Introduction: Percutaneous left atrial appendage closure (LAAC) in AF patients is not inferior to oral anticoagulation (OAC) in terms of systemic embolism. LAA Closure is usually contraindicated in presence of intracardiac thrombus, a condition far from uncommon. The feasibility and safety of transcatheter cerebral embolic protection (TCEP) has been reported in literature as a successful off – label option in retrieving embolic debris during percutaneous LAAC. We present two cases of Watchman Flex insertion in the setting of LAA thrombus and prophylactic use of TCEP. Cases report: The first patient was an 88-year-old male with history of symptomatic AF and post – traumatic cerebral bleeding, who was referred to LAAC because of high risk of bleeding in using OAC. Transthoracic echocardiography (TTE) documented a severely dilatated left atrial and preserved left ventricular systolic function. Transesophageal echocardiography (TEE) revealed a " chicken wing " shaped LAA with spontaneous echo-contrast and sludge effect confirmed with echo-contrast medium " SonoVue ". ECG – gated cardiac CT (CCT) showed a LAA filling defect and confirmed the diagnosis of LAA thrombus. The second patient was a 75-year-old man with valvular permanent AF and history of multiple ischemic strokes despite of OAC therapy with Warfarin. TTE documented a dilated left ventricle with severely depressed ejection fraction; TEE revealed a " windstock " shaped LAA with incompletely distal opacification with echo-contrast medium " SonoVue ". Both patients were candidate to LAAC with concomitant use of CEPDs in the event of neurological complication. TriGUARD 3 cerebral protection (TG3, Keystone Heart) was deployed in the aortic arch through right femoral artery access before LAAC procedure. Following transseptal puncture Watchman Flex device (Boston Scientific, Marlborough, MA) was deployed without complications or residual peri-device leaks. At the end the TriGurad 3 device was retracted and no debris were noted at the post operatory inspection. The first patient was discharged afterward with daily acetylsalicylic acid 100 mg and Clopidogrel 75 mg and the second patient with daily acetylsalicylic acid 100 mg and Warfarin. Both patients underwent follow-up TEE at four weeks. Neither device – related complications nor thrombotic/hemorrhagic adverse events have been not reported so far. Discussion: Both patients were at very high risk for stroke and bleeding. They were not theoretically candidate to LAAC because of intracardiac thrombus. The prophylactic use of TCEP (including TG3) has been reported in a small retrospective study by Tarantini et al. and in some case series. Procedures were always successful and uneventful. Moreover, small captured debris on the device on visual examination proved its efficacy. The use of TCEP has been mentioned even by Beneduce et al. as a safer and more feasible strategy in AF patients. Conclusion: Prophylactic use of TCEP during The Watchman Flex device implantation is safe and feasible.